2015
DOI: 10.1111/bjh.13766
|View full text |Cite
|
Sign up to set email alerts
|

Excellent outcomes and lack of prognostic impact of cell of origin for localized diffuse large B-cell lymphoma in the rituximab era

Abstract: Summary Therapeutic options for limited-stage diffuse large B cell lymphoma (DLBCL) include short- or full-course R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) +/- radiotherapy. The optimal treatment remains unclear. The prognostic value of cell-of-origin (COO) in early stage DLBCL is unknown. Patients with limited-stage DLBCL (stage I or stage II, non-bulky) treated with R-CHOP +/- involved field radiotherapy (IFRT) from 1999 – 2012 were included. COO by the Hans algorithm was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 29 publications
2
15
1
Order By: Relevance
“…22 The current study is the first multicenter analysis to focus specifically on LS-DLBCL/HGBL with MYC-R and/or BCL2-R and/or BCL6-R within 1 radiation field. Although the 2-year PFS and OS in our cohort (78% and 86%, respectively) were lower than historical cohorts of LS-DLBCL, 23,24 they are significantly better than previous reports that included patients with advanced-stage MYC-R DLBCL/HGBL and DHL. 17,19 We excluded LS patients with MYC-R with disease outside of 1 radiation field to limit heterogeneity of disease, minimize bias that could be involved in frontline therapy selection (ie, treating physician may tend to use IIC in stage 2 disease outside of 1 radiation field with adverse cytogenetics), and allow direct comparison of patients treated with and without radiation therapy.…”
Section: Discussioncontrasting
confidence: 86%
“…22 The current study is the first multicenter analysis to focus specifically on LS-DLBCL/HGBL with MYC-R and/or BCL2-R and/or BCL6-R within 1 radiation field. Although the 2-year PFS and OS in our cohort (78% and 86%, respectively) were lower than historical cohorts of LS-DLBCL, 23,24 they are significantly better than previous reports that included patients with advanced-stage MYC-R DLBCL/HGBL and DHL. 17,19 We excluded LS patients with MYC-R with disease outside of 1 radiation field to limit heterogeneity of disease, minimize bias that could be involved in frontline therapy selection (ie, treating physician may tend to use IIC in stage 2 disease outside of 1 radiation field with adverse cytogenetics), and allow direct comparison of patients treated with and without radiation therapy.…”
Section: Discussioncontrasting
confidence: 86%
“…21 It was recently reported that in contrast to advanced stage DLBCL, the cell-of-origin is not prognostic in limited stage disease. 9,13 To impact prognosis of these good risk patients, a biomarker, such as MYC breaks, might be helpful. 12 We found an MYC translocation in 3 of 11 evaluable relapsed cases.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the generally favourable outcome, relapses still occur in 10 to 20% of patients with limited stage DLBCL and 5-year OS ranges between 75% and 94%, which suggests that salvage of relapses is frequently unsuccessful. [6][7][8][9][10] Clinical prognostic models only partially identify patients at risk for relapse. 2,11 Biological tumour characteristics such as cell of origin and especially presence of MYC translocation have prognostic significance in DLBCL.…”
mentioning
confidence: 99%
“…These biologic features may affect the selection of CNS prophylaxis in primary breast DLBCL patients. Given the recent retrospective data that appropriately selected limited-stage DLBCL (i.e., completely resected or interim PET-negative lymphomas) might be successfully treated with short-course immunochemotherapy without radiotherapy [25,26], a large subgroup of patients who did not have any biologic features for poor clinical outcomes might have excellent outcomes with a low risk for CNS failure. These patients may be eligible for study with de-escalating treatment strategies.…”
Section: Discussionmentioning
confidence: 99%